Calibrating relative velocity and lateral clearance parameters of a lane changing model for traffic microsimulation - Dimayacyac, Eugene T.
Traffic simulation is currently one of the most used and proven effective tool in traffic management. Its ability to emulate vehicles and other associated elements with the corresponding time variabi lity and faculty for interfacing with the surroundings made traffic simulations suitable and distinctly adaptable for evaluation, planning, and analysis of complex transportation systems. Herewith, the Department of Science and Technology (DOST) in the Philippines has proposed a project which aims to develop a local traffic simulation which will be initially implemented in EDSA. Nevertheless, the lane changing model, which is a subcomponent of the local simulations, is currently inadequate of several threshold parameters which is the lateral clearance maintained between vehicles and the limit velocity difference. Consequently, the study intends to determine the parameters required for the lane changing model through video surveillance with the aid of various statistical methods. Scatter plots and frequency distributions of the parameters were generated for different types of vehicles.